The wind of change : Harold Macmillan and British decolonization - Butler, L. J. (Lawrence J.); Stockwell, S. E. (Cambridge imperial and post-colonial studies series., 2013)
"Harold Macmillan's 'Wind of Change' speech, delivered to the South African parliament in Cape Town at the end of a landmark six-week African tour, presaged the end of the British Empire in Africa. This book, the first to focus on Macmillan's 'Wind of Change', comprises a series of essays by leading historians in the field. Contributors reconsider the significance of the speech within the politics of different overseas and British constituencies, including in the wider British World. Some contributors engage directly with the speech itself - its metropolitan political context, production, delivery and reception. Others consider related themes in the historiography of the end of empire. Together they challenge established orthodoxies and offer fresh perspectives that require us to revisit our understanding of the place of the speech, and the policies to which it referred, in the wider history of British decolonization"--